miRNA-Based Potential Biomarkers and New Molecular Insights in Ulcerative Colitis - Zhou, Jing; Liu, Jialing; Gao, Yangyang; Shen, Liwei; Li, Sheng; Chen, Simin (Frontiers in Pharmacology, 2021)
Ulcerative colitis (UC) is a chronic non-specific inflammatory bowel disease, which usually manifests as abdominal pain, diarrhea and hematochezia. The disease often recurs and is difficult to cure. At present, the pathogenesis is not clear, but it is believed that the disease is caused by a complex interaction among immunity, heredity, environment and intestinal microflora disorders. MicroRNA (miRNA) is endogenous single-stranded non-coding RNA of 17–25 nucleotides (nts). They target the 3'Untranslated Region of a target gene and inhibit or degrade the target gene according to the extent of complementary bases. As important gene expression regulators, miRNAs are involved in regulating the expression of most human genes, and play an important role in the pathogenesis of many autoimmune diseases including UC. Studies in recent years have illustrated that abnormal expression of miRNA occurs very early in disease pathogenesis. Moreover, this abnormal expression is highly related to disease activity of UC and colitis-associated cancer, and involves virtually all key UC-related mechanisms, such as immunity and intestinal microbiota dysregulation. Recently, it was discovered that miRNA is highly stable outside the cell in the form of microvesicles, exosomes or apoptotic vesicles, which raises the possibility that miRNA may serve as a novel diagnostic marker for UC. In this review, we summarize the biosynthetic pathway and the function of miRNA, and summarize the usefulness of miRNA for diagnosis, monitoring and prognosis of UC. Then, we described four types of miRNAs involved in regulating the mechanisms of UC occurrence and development: (1) miRNAs are involved in regulating immune cells; (2) affect the intestinal epithelial cells barrier; (3) regulate the homeostasis between gut microbiota and the host; and (4) participate in the formation of tumor in UC. Altogether, we aim to emphasize the close relationship between miRNA and UC as well as to propose that the field has value for developing potential biomarkers as well as therapeutic targets for UC.